Patient Attitudes Toward Testicular Prosthesis Placement After Orchiectomy - Srivatsav, Ashwin (Am J Mens Health, 2019)
Orchiectomy is the standard of care for many testicular conditions. Testicular prosthesis placement (TPP) can mitigate psychosocial burden, restore self-image, and improve quality of life for patients requiring orchiectomy. Limited data exist regarding patient attitudes and counseling on TPP in the United States. The objective of this study was to characterize patient experiences after TPP, rationale for pursuing/declining TPP, and satisfaction levels. Patients with a history of urologic conditions warranting orchiectomy were identified and sent an anonymous survey addressing demographics, pre/post counseling, attitudes toward TPP, satisfaction rates, and postoperative complications. Sixteen percent (76/480) of patients completed the survey. Of these, 50.8% (32/63) undergoing orchiectomy were counseled by their surgeon about TPP, and 22.2% (14/63) received a prosthesis. The most common reasons for declining TPP included lack of concern for cosmetic appearance and lack of counseling. Leading reasons for pursuing TPP included improving self-confidence and cosmetic appearance. Although 71% (10/14) of patients were satisfied with TPP, they did highlight areas for improvement. Twenty percent (2/10) felt their implant was too high, 60% (6/10) felt their implant was too firm, 10% (1/10) endorsed discomfort during sex, and 30% (3/10) felt that TPP did not match their size expectations. Despite these findings, 71% (10/14) reported that they would have TPP again and 79% (11/14) would recommend TPP to others. TPP improves body image and quality of life following orchiectomy. Provider counseling plays an important role in influencing a patient’s decision to undergo TPP. Areas of improvement include implant positioning and more effective replication of testicular consistency.